Penjernihan Air Bersih dengan Filter Alami dan Aerasi di Teluk Bakung, Sungai Ambawang, Kubu Raya - Mochamad Hilmy; Herry Prabowo (LPPM UMRI, 2020)
Fresh water is a vital requirement in human daily life. Teluk Bakung Village relies on fresh water supplies from the Ambawang River and wells made by the community. The condition of well water in Teluk Bakung Village tends to be the color of ground water which is influenced by the roots of trees, blackish brown and high iron content. The purpose of this Community Service activity is to carry out water filtration on gambut soil to improve the condition of fresh water sources at Al-Muhajirin Mosque in Mu'allaf village, Teluk Bakung Village, Sungai Ambawang District, Kubu Raya Regency, Kalimantan Barat as meeting the mosque's needs and the society. The method of applying IPTEKS is by transferring IPTEKS by improving the physical condition of the Al-Muhajirin Mosque building, the application of clean water filtration as well as training the local staffs for operations and maintenance as well as the plumbing network. It is expected that the addition of aeration system groundwater that has iron content will make it clearer than just filtration which has been carried out at that location.